Analysis of the Influence of Workload and Work Stress Determinants on Personnel Performance through Work Motivation (A Study at the Regional Police of Lampung) - Hakim, Lukmanul; Fajar Destri Prasetyo; Anuar Sanusi; M. Hasan Ma'ruf (JURNAL ILMIAH EDUNOMIKA, 2025)
The performance of police personnel serves as a key indicator in determining the effectiveness of law enforcement organizations in carrying out their duties and functions. The complex and high-pressure nature of police work poses significant challenges that may affect the stability and productivity of personnel performance. High workload and psychological pressure resulting from job stress can have both direct and indirect impacts on performance. Work motivation plays a strategic role as a mediating variable that can either strengthen or weaken the influence of these determinants on performance. The research problem addressed in this study is: how do workload and job stress affect the performance of personnel at the Lampung Regional Police (Polda Lampung), both directly and indirectly through work motivation as an intervening variable? This study employs a quantitative approach using the Partial Least Squares (PLS) Structural Equation Modeling (SEM) method with SmartPLS version 4.0. The results reveal that workload has a significant positive effect on personnel performance, while job stress does not. Additionally, personnel performance does not have a significant positive effect on work motivation. Moreover, workload and job stress do not significantly influence personnel performance through work motivation. Keywords: Workload Determinants, Job Stress, Personnel Performance, Work Motivation